2021
DOI: 10.1021/acs.est.0c08766
|View full text |Cite
|
Sign up to set email alerts
|

Cometabolic Vinyl Chloride Degradation at Acidic pH Catalyzed by Acidophilic Methanotrophs Isolated from Alpine Peat Bogs

Abstract: Remediation of toxic chlorinated ethenes via microbial reductive dechlorination can lead to ethene formation; however, the process stalls in acidic groundwater, leading to the accumulation of carcinogenic vinyl chloride (VC). This study explored the feasibility of cometabolic VC degradation by moderately acidophilic methanotrophs. Two novel isolates, Methylomonas sp. strain JS1 and Methylocystis sp. strain MJC1, were obtained from distinct alpine peat bogs located in South Korea. Both isolates cometabolized VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The maximum growth rate of the Methylocystis sp. MJC1 in the exponential growth phase was 0.12 h -1 , which is higher than the previously reported cell growth rate of MJC1 (0.063 h -1 ) cultured in DNMS (dilute nitrate mineral salts) medium with the addition of copper [ 18 ]. During 4 days of fermentation, the Methylocystis sp.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The maximum growth rate of the Methylocystis sp. MJC1 in the exponential growth phase was 0.12 h -1 , which is higher than the previously reported cell growth rate of MJC1 (0.063 h -1 ) cultured in DNMS (dilute nitrate mineral salts) medium with the addition of copper [ 18 ]. During 4 days of fermentation, the Methylocystis sp.…”
Section: Resultsmentioning
confidence: 55%
“…The growth rate of Methylocystis sp. MJC1 has been reported to be up to 0.063 h -1 when copper was added to the medium [ 18 ]. Interestingly, the maximum growth rate (0.12 h -1 ) was higher in the copper-less medium, indicating potentially higher growth rates in the presence of active sMMO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for acidophilic methanotrophs to biodegrade pollutants is largely unknown, and evaluation of potential applications of these organisms has just begun in recent years (Choi et al, 2021 ; Semrau, 2011 ; Shao et al, 2019 ; Szwast, 2021 ). This pursuit is important, particularly for chlorinated solvents because, as previously noted, traditional bioremediation approaches are not as effective at low pH for completely dechlorinating CVOCs, particularly chlorinated ethenes.…”
Section: Potential Bioremediation Applications In Low Ph ...mentioning
confidence: 99%
“…is largely ineffective at reducing chlorinated ethenes to ethene in naturally acidic aquifers, because it is typically inhibited at pH < ~5.5 (Eaddy, 2008 ; Lacroix et al, 2014 ; Rowlands, 2004 ; Steffan & Vainberg, 2013 ; Vainberg et al, 2009 ; Yang, 2012 ; Yang et al, 2017 ). Although much more research is required, acidophilic methanotrophs have recently been observed to degrade a range of CVOCs at pH <5.5, suggesting that cometabolic treatment may be an option for CVOCs and other contaminants in acidic aquifers (Choi et al, 2021 ; Semrau, 2011 ; Shao et al, 2019 ; Szwast, 2021 ).…”
Section: Introductionmentioning
confidence: 99%